PERHITUNGAN PERKIRAAN KEBUTUHAN TEMPAT TIDUR BANGSAL KUTILANG RSUP DR KARIADI SEMARANG - Desi Syahbaniar; Ervina Rachmawati; Feby Erawantini (Politeknik Negeri Jember, 2021)
Dr. Kariadi Public Hospital has 44 inpatient Wards. Kutilang Ward has quite high number of BedOccupancy Rate (BOR) during 2017-2019. The purpose of this study was to determine bed requirementsin Kutilang Ward dr.Kariadi Public Hospital Semarang for 3 years (2020-2022) by using analysis of trendsregression linear (least square) method. This research was a descriptive study, with methods ofobservation and interviews. The object of research was inpatients recapitulation data on Kutilang dasarward and Kutilang 1 ward. The research subjects were Analising and Reporting officers in Dr KariadiPublic Hospital. The result showed that the needs of bed in Kutilang dasar ward in the year 2017 - 2019was 1 unit, Kutilang 1 ward need 31-63 units. The solution is the hospital management should consider toadd more the patient’s bed needs.